Active Light‐Powered Antibiofilm ZnO Micromotors with Chemically Programmable Properties. (21st April 2021) - Ussia, Martina; Urso, Mario; Dolezelikova, Kristyna; Michalkova, Hana; Adam, Vojtech; Pumera, Martin
Abstract: Bacterial biofilms are multicellular communities firmly attached to solid extracellular substrates. They are considered the primary cause of huge economic losses, from medicine due to medical implants' failure to large infrastructure due to enhanced pipe corrosion. Therefore, their eradication is highly desirable. Here, the preparation of ZnO self‐propelled micromotors is reported, programming their morphology and motion properties through Ag doping. The ZnO:Ag micromotors actively move upon light irradiation via a self‐electrophoretic mechanism, showing excellent light‐controlled on/off switching motion. At the same time, the rapid and effective removal of both gram‐positive and gram‐negative bacteria biofilms from the solid surface is demonstrated, exploiting the well‐known antibacterial activity of both Ag and ZnO as well as the enhanced diffusion of the micromotors. The new concept for the low‐cost and scalable preparation of chemically programmable Ag‐doped ZnO micromotors here illustrated opens a new route toward the formulation of a new class of light‐driven semiconducting self‐propelled micromotors for environmental applications. Abstract : Controlled doping of ZnO microparticles with Ag allows the formulation of intrinsically asymmetric micromotors able to autonomously move under UV‐light irradiation via a self‐electrophoretic mechanism. The self‐propelled microswimmers show the effective eradication of gram‐positive and gram‐negative bacterial biofilms from solid surfaces by increased solution mixing, enhanced ROS generation, and the rapid release of Ag ions in water.